Extraction of nigella sativa using modern hydrodistillation technique - Mohd Aizudin, Abd Aziz (2006)
Nigella Sativa (Jintan Hitam) can produce essential oil that is important in medicine and also important in developing our agriculture sector nowadays. To obtain Nigella Sativa essential oil, entrepreneur and researcher nowadays use hydro distillation method. So the objective of this study is to obtain essential oil from Nigella Sativa plant source using modern hydro distillation technique because of it market values, by investigating and understanding hydro distillation extraction process. For this research, the rotary evaporator will be use and the parameters which are expected to dominate in producing high yield of Nigella Sativa oil was the effect of time and the surface area of the Nigella Sativa seeds expose to the extraction process. The temperature for the extraction process is maintained at 100 o C and 1 bar for the pressure. It is expected that the optimum operating time will be establish from the experimental result. The main compound of the essential oil is Thymoquinone, which are around 50% from overall compounds.Therefore, the presence this compound should take as a characteristic for the essential oil and the essential oil will analyze using High Performance Liquid Chromatography (HPLC)